WAR THROUGH CHILDREN’S EYES - Amirhanova, M M (History, Archeology and Ethnography of the Caucasus, 2015)
The article is devoted to the memories of the "war children" whoknew to own cost the hardships of the iron years of the war. In accordance with the law "State social assistance to war children", war children are considered to be the citizens of the Russian Federation, who were under 18 years of age by the time of the end of World War II (September 2, 1945). Their memories and eyewitness accounts allow to reconstruct many-sided picture of the hardships endured by the Russians during the war. They highlight various aspects of the lives of adults and children at that severe war time. The materials of local periodical press presented by U.I. Akhberdieva tell us about the first hours of the war in Western Ukraine. All the authors recall the incredible severities of the war years in everyday life. There was lack of fuel, clothes, footwear, etc. S.H. Akhmedov’s recollection shows that the war children’s brightest joyful flashback was Victory Day. Despite the fact that many people had lost their relatives during the war it was truly a national holiday.